Development the Influence of Leadership Commitment and Performance of Principals and Teachers on the Model of Improving Quality of Education - Sukmana, Aditya Hendra; Pramono, Suwito Eko; Utanto, Yuli (Universitas Negeri Semarang, 2024)
Education is the main foundation in the development of quality human beings and society. Judging from the facts on the ground, there are many problems in the field of education. One of the problems of education is the low quality of education at various levels of education, both formal and informal. This study aims to find and analyze the direct influence of teacher commitment on the quality of education and find and analyze the direct influence of teacher performance on the quality of education. This study uses field research with a quantitative approach. The preparation of research instruments begins with a theoretical study of various concepts, theories and opinions of experts. In this study, to test the validity given to the respondents, it was first tested on students outside the sample of 10 people each. To obtain complete, valid and reliable data, the researcher uses three methods, namely the Observation Method, the Questionnaire/Questionnaire Method and the Documentation Method. The results of this study are Based on the results of research and calculations proving that there is an influence between the principal's leadership variables on teacher performance at SMP IT Insan Madani, seen from the test of the persial test (T-Test), the results of the Tcount value of 3.232 and the Ttable value of 2.042 with a significance value of 0.003. With the test criteria of Tcount > Ttable and if the Significance < 0.05 then H0 is rejected. The findings of this study will inform the development of targeted interventions aimed at enhancing teacher commitment and performance, ultimately leading to improved educational outcomes